How can emerging tennis nations survive the tennis arms race? My thoughts through a strategic lens! - Cahill, G. (Coaching and Sport Science Review, 2024)
This article provides an opinion of the current challenges and unique perspectives experienced by emerging tennis federations. It delves into a comprehensive analysis around strategic development derived from qualitative research involving esteemed individuals in the field, including senior leaders, national coaches, and board members from two distinct nations: Tennis Malaysia and Tennis Ireland. Through this investigative journey, numerous critical challenges have emerged, shedding light on the intricate landscape that smaller federations navigate. The article offers some practical applications for federations to consider when making strategic decisions.